Optimalisasi Pengelolaan Jurnal Ilmiah Elektronik Menuju Jurnal Bereputasi di IAIN Sultan Amai Gorontalo - Habibie, Alvons; Ismail, Abdul K. (LP2M IAIN Sultan Amai Gorontalo, 2024)
Abstract: This study aims to optimize the management of electronic-based scientific journals at IAIN Sultan Amai Gorontalo toward becoming nationally accredited and internationally reputed journals. The optimization was carried out through a series of activities consisting of journal roadshows, sharing sessions, and workshops involving 38 journal editors within IAIN Sultan Amai Gorontalo. The implementation method includes five main activities: (1) Journal roadshow for strengthening journals and publications, (2) First sharing session on editorial and review processes, (3) Second sharing session on writing tools and global indexing, (4) Third sharing session on journal website design and manuscript management, and (5) Workshop on electronic journal management based on Arjuna assessment. The results show significant progress in journal management capabilities, including the establishment of editorial teams displayed on each journal's OJS layout, strengthened understanding of OJS 3 management, improved knowledge of writing tools implementation, and enhanced journal website appearances. Additionally, several journals have successfully submitted to DOAJ and other indexing institutions, marking a step forward towards achieving national and international journal reputation.